2018
DOI: 10.1159/000487668
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Brain Atrophy on Early Neurological Deterioration and Outcome in Severe Ischemic Stroke Treated by Intravenous Thrombolysis

Abstract: Background: Brain atrophy has shown a protective effect on the risk of early neurological deterioration (END) related to malignant edema in patients with hemispheric infarction but could be deleterious on the outcome. Aims: We aimed to assess whether brain atrophy has an impact on the risk of END and on the outcome in severe ischemic strokes after intravenous (IV) thrombolysis. Methods: From a prospective thrombolysis registry, 137 patients who had a National Institutes of Health Stroke Scale (NIHSS) ≥15, MRI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…Evidence showed that it would cause a loss of resilience to acute health problems, which may result from both the diseases and extrinsic stressors ( Bu et al, 2021 ). Brain frailty is detected on neuroimaging or postmortem as atrophy and markers of cerebral small vessel disease (CSVD), including white matter hyperintensities (WMHs), lacunes, enlarged perivascular spaces (EPVSs), lacunar infarcts, and microbleeds ( Tschirret et al, 2018 ; Appleton et al, 2020 ). These brain parenchyma lesions can cause an acute stroke syndrome known as lacunar stroke, or more subtle pathological alteration, which may eventually lead to neurological deficits and cognitive decline in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence showed that it would cause a loss of resilience to acute health problems, which may result from both the diseases and extrinsic stressors ( Bu et al, 2021 ). Brain frailty is detected on neuroimaging or postmortem as atrophy and markers of cerebral small vessel disease (CSVD), including white matter hyperintensities (WMHs), lacunes, enlarged perivascular spaces (EPVSs), lacunar infarcts, and microbleeds ( Tschirret et al, 2018 ; Appleton et al, 2020 ). These brain parenchyma lesions can cause an acute stroke syndrome known as lacunar stroke, or more subtle pathological alteration, which may eventually lead to neurological deficits and cognitive decline in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms for END have been largely undefined, thus limiting the effective prevention and treatment of END. Previous studies have shown that END in the acute phase of AIS was associated with the severity of stroke on admission as measured by the National Institutes of Health Stroke Scale (NIHSS) ( 7 ), treatment delay ( 8 ), and less optimal treatment strategies ( 9 , 10 ). Although the EVT techniques have been well-developed and implemented broadly in major stroke centers in the world in recent years with short door-to-needle time (DNT) and improved patient outcome with AIS, END remains highly unpredictable and insidious clinically.…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of BV and/or CSV can quantify the degree of brain atrophy ( 72 , 77 , 78 ). The DWI high-intensity volume/BV ratio and cerebral blood volume lesion volume/CSV ratio have been demonstrated as reliable predictive markers for malignant MCA infarction, with a cut-off value of 0.078 (sensitivity 86%, specificity 87%) and 0.92 (sensitivity 96.2%, specificity 96.2%), respectively ( 72 , 79 ).…”
Section: Neuroimaging Predictors Of Edemamentioning
confidence: 99%
“…Intercaudate distance (ICD) is considered a convenient and practical marker for brain atrophy ( 80 ), and a higher ICD has been shown to be a protective factor against malignant infarction ( 74 , 78 , 80 ). Lee et al demonstrated that an ICD ≥ 20 mm in the non-infarcted hemisphere has an independent protective effect against malignant clinical outcomes during admission to hospital.…”
Section: Neuroimaging Predictors Of Edemamentioning
confidence: 99%